A mini-review on recent trends in prospective use of porous 1D nanomaterials for hydrogen storage - Chingis Daulbayev (Elsevier, 2022)
The sustainable development of hydrogen energy is a priority task for a possible solution to the global energy crisis. Hydrogen is a clean and renewable energy source that today is used exclusively in the form of compressed gas or in liquefied form, which prevents its widespread use. Storing hydrogen in solid-state systems will not only increase the bulk density and gravimetric capacity, but will also have a positive impact on safety issues. From this point of view, the current review considers the latest research in the field of application of 1D nanomaterials for solid-state hydrogen storage, and also discusses the mechanisms of its adsorption and desorption. Despite the high publication activity, the use of 1D nanomaterials for hydrogen storage has not been fully studied. In the current review, modern developments in the field of hydrogen storage using 1D nanomaterials and composites based on them are investigated in detail, and their problems and future prospects are discussed.